Influence of sintering temperatures on material properties and corresponding milling machinability of zirconia ceramics. (August 2021) - Ji, Min; Xu, Jinyang; Yu, Dedong; Chen, Ming; El Mansori, Mohamed
Abstract: Sintering is a comprehensive process that involves complex evolution of material microstructures and properties, being recognized as a key factor to improve the machinability of ceramics. The present study aims to address the densification mechanisms of 3 mol% yttria-stabilized tetragonal zirconia polycrystal (3Y-TZP) based on the properly designed sintering experiments. The impacts of sintering temperature on the grain growth, phase composition, and mechanical properties were rigorously studied. A particular focus is placed on identifying the correlations between the sintering scheme and the machinability of 3Y-TZP by conducting a series of milling tests. The acquired results indicate that the porous zirconia begins to crystallize at 1100 °C and gradually converts to ceramic characteristics after 1200 °C, resulting in a significant increase of cutting forces and temperatures. Moreover, the zirconia sample sintered at 1200 °C exhibits obvious ductile-brittle removal characteristics and moderate hardness. Thus, a precise control of the machined surface quality can be achieved by cutting within the ductile regime.